Ir Man Enterprise / Nur Azia Shazni Shaari - Shaari, Nur Azia Shazni (2020)
In order to fulfill the task given for Fundamental of Entrepreneurship (ENT300), I need to carry out some information that requires by case study to enhance my skill in communication and the way to overcome the characteristics in the field of business itself. After I make some survey that needed by this case study, I decided to contact one of the companies that I know well in the business field. So, I already enter into interview session with owner of the company IR MAN ENTERPRISE, Mr. Kaharuddin bin Sulaiman. From the interview, Mr Kaharuddin has given detail explanation about his business and how he been encouraged to become a businessman in young age. I also take down information about his personal detail, career, and his company background such as organizational structure, type of business model, product or services marketing and operational strategy. Another than that, I also can identified the entrepreneur characteristic on founder of IR MAN ENTERPRISE such as problem solving, efficiency orientation, persuasive and so on.